Direct endoscopic necrosectomy in infected pancreatic necrosis using lumen-apposing metal stents: Early intervention does not compromise outcome - Albers, David; Meining, Alexander; Hann, Alexander; Ayoub, Younan Kabara; Schumacher, Brigitte (Endoscopy International Open, 2021)
Background and study aims Infection of pancreatic necrosis is a dreaded complication requiring an intervention. Nevertheless, the optimal timing of the first intervention is unclear, and consensus data are sparse. This retrospective two-center study evaluated direct endoscopic necrosectomy using lumen apposing metal stents in case of proven or suspected infected pancreatic necrosis in an early stage of the disease.Patients and methods Forty-nine patients with infected pancreatic necrosis were included. Sequent direct endoscopic necrosectomies after lumen apposing metal stent insertion (LAMS) were performed until the resolution of necrosis. In all patients, the first endoscopic intervention was performed within the first 30 days after first proof of pancreatic necrosis. Primary outcome parameters were inflammatory activity, days spent in the Intensive Care Unit (ICU), and mortality.Results The patient cohort received median 4 necrosectomies (3–5) after a median of 7 days (3–11) after first proof of pancreatic necrosis. Technical and clinical success were achieved in 98.3 % and 87.8 %, respectively; the mortality rate was 8.2 %. The median C-reactive protein level decreased from 241 mg/L (182.9–288.9) before the intervention to a median of 23.3 mg/L (18–60) after therapy. The median time period in the ICU was 5 days (3–9).Conclusions Early endoscopic therapy in the form of direct endoscopic necrosectomy after LAMS placement within the first 30 days after proof of pancreatic necrosis is effective and does not result in poor outcome. Our retrospective data suggest that early intervention before walled-off necrosis is formed is tenable when it is essential due to the patient's clinical deterioration.